Three essays about health progress and economic development in Africa - (:unkn) unknown (My University, 2015)
This dissertation aims at opening the black box of African health progress during and followingthe colonial period. It does so by making three contributions to the literature on health policies,health standards and fertility patterns, in the 20th century’s Africa.The first chapter compares the colonial strategies for health policies’ provision and other colonialpolicies in former FrenchWest Africa between 1904 and 1958. Drawing on colonial archivesand existing data, it gathers a unique dataset containing colonial inputs at the colonial districtlevel: medical and educational staff, vaccinations, public work’s expenses and conscription.There was a very general strategy as regards to the provision of colonial services. In this context,the allocation of health inputs was specific in two dimensions only. First, medical staffwas used as a means of colonial “coverage”. Second, there is a long-lasting effect of preventionleading to a “diversification” strategy for all health investments. Away from these specificities,the common factors to all investments have to do with the colonial administration’s preferencefor path dependence, investments’ returns to scale, the diseases’ contagion risk and the demandfor colonial services. This work also suggests that there was no specialization of districtsin one type of investments.The second chapter of this thesis looks at the relationship between adult height and underfivemortality in the context of the “double African Paradox” in West Africa. Africans arerelatively tall in spite of extremely unfavorable income and disease environments. Moreover,their height stature decreased since the 1960’s despite improving health conditions and a fallin under-five mortality rates. This study points to selective mortality, by bringing forward apositive correlation between mothers’ height and mortality in the 1980’s West Africa. It thenestimates a new model of height differential between survivors and dece
Keywords: African Research